Bexagliflozin – evaluation of the clinical efficacy, safety profile and potential new applications of the SGLT2 inhibitor: a review of the literature (Journal of Medical Science, 2025)
Introduction. Type 2 diabetes (T2DM) is a growing global health, social, and economic problem. T2DM is often accompanied by other diseases and is associated with complications such as kidney damage and cardiovascular diseases. The 21st century has seen a breakthrough in treating T2DM, including incretins and flozins. This review focuses on bexagliflozin, a new SGLT-2 inhibitor approved by the FDA for treating T2DM. The efficacy, safety, and potential benefits of new uses are analysed. Materials and methods. Sources were obtained using PubMed and Google Scholar, as well as Medline, with the keywords: bexagliflozin, EGT1442, new indications for bexagliflozin, and bexagliflozin trials. Results. Unlike other SGLT-2 inhibitors, bexagliflozin has a different molecular structure, which may increase its selectivity and efficacy. Preliminary results suggest that the drug may offer additional therapeutic benefits over other drugs in this group, particularly in the treatment of hypertension and cardiac arrhythmias. Studies are currently underway to investigate its potential use in the treatment of chronic kidney disease in children and sleep apnoea. Conclusions. Bexagliflozin shows promise as a treatment for type 2 diabetes, with additional potential benefits in treating other conditions. Although the drug is relatively new to the market, preliminary studies indicate that it may offer advantages over other SGLT-2 inhibitors in some areas. Nevertheless, further clinical trials are needed to further evaluate its efficacy compared to other therapies and its potential in a broader range of applications